RELATIONSHIP BETWEEN NIGHT-TIME DYSPNEA EPISODES AND HEART RATE VARIABILITY - Szabó, Krisztina; Balogh, László; Ihász, Ferenc (Stadium - Hungarian Journal of Sport Sciences, 2020)
Purpose: We wanted to assess the values of expected night-time and day-time variability of the heart rate, in the presence of dyspnea episodes during night-time, recorded by a Holter monitor. Objective: Our aim was to investigate whether nocturnal breathing disorders affect the HRV indexes. Methods: 40 patients participated in our survey. 20 of them experienced episodes of night-time breathing difficulty, and the control group consisted of 20 participants in whose case there were no episodes of night-time breathing difficulty. We were examining the domains of time and frequency of heart rate variability, using day-time and night-time values recorded by a 24-hour Schiller Medilog Holter monitor. We evaluated the distribution of the parameters with a continuous codomain, their typical distribution and expected values on histograms, and summarized them in a table. For the examination of the difference in averages the Two-Sample T- Test was used, where p<0.05. Results: The vegetative equilibrium ratio and the standard deviation of the R-R intervals showed a significant difference between the apnea patients and the healthy group at night. Examining the severity of apnea, we didn’t find significant difference between the two groups in the mean of the time and frequency indices, however, a decrease in the values of the apnea group was observed compared to the control group. Conclusion: Night differences in the vegetative equilibrium rate and time parameters of the apnea patients and the control group, as well as differences in the HRV index recorded by the change in the severity of the disease, draw attention to the importance of the HRV indicators with HOLTER monitors.